Brucellosis or contagious abortion - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Dr Edward Okoth, Head of biological services at the International Livestock Research Institute, Nairobi.